Impact of freezing, on some basic components of marine fish flesh (Rabbit fish) caught from the Syrian marine water. - Saad, Adib; Ali, Ali; Mohamad, Rana (Latakia University Journal -Biological Sciences Series, 2013)
This work was designed to investigate the effect of temperature of frozen storage and its duration on some chemical properties (Protein, Ash, Moisture,Lipid) of fishes Rabbit fish (Siganus rivulatus). The fishes were subjected (from one weak to 150 day) of frozen storage at two different degrees of low temperatures (-18 C,-24 C). Chemical analysis were done including evaluation of (Protein, Ash, Moisture, Fat), for study type and the two freezing degree during the following freezing periods/7, 15, 30, 45, 60, 90, 120, 150 day/. The study was carried out between September 2011 and May 2012 in Technical Engineering Faculty in Tartus , Tishreen University.Protein gradually decreases with increasing duration of frozen storage,compared with the fresh samples which recorded (20.6%) ,while (17.03, 17.99%) were recorded for fish samples that were frozen for (150) day at(-24, -18 C). On the other hand, The study showed no change in percentage proportions of ash during freezing duration for samples our study type and at the two freezing degrees /-24, -18 C/,compared with the fresh samples. The study showed a decrease of the percentage of moisture in the first periods of storage and then arise in recent periods of freezing. The study showed a clear decrease with the percentage of fat from the first week freezing until the end of the freezing duration,for samples our study type and at the two freezing degrees /-24, -18 C/,while the percentage of fat which frozen for /7, 150/ day respectively at /-24 C/was /7.12, 3.3%/, and at /-18 C/ was/ 7.12, 3.36%/.Note that this apparent decrease of fat percentage was faster when freezing at /-18 C/ compared with freezing at /-24 C/.